ナンキョク サウスシェトランド ショトウ デノ コガタ ムジン ヒコウキ Ant-Plane ノ ヒコウ ト クウチュウ ジキ コウクウ シャシン カンソク - 船木, 實; フナキ, ミノル; 東野, 伸一郎; ヒガシノ, シンイチロウ; 坂中, 伸也; サカナカ, シンヤ; 岩田, 尚能; イワタ, ナオヨシ; 中村, 教博; ナカムラ, ノリヒロ; 平沢, 尚彦; ヒラサワ, ナオヒコ; et al. (2013)
P(論文) 模型飛行機の部品と技術を応用し,2種類の小型無人飛行機,Ant-Plane 3と6を開発した.2011年1月,南極キング・ジョージ島(King George Island)でブランスフィールド海盆(Brans?eld Basin)の空中磁気観測を計画したが,悪天候等で満足できる飛行ができなかった.2011年12月にはリビングストン島(Livingston Island)にあるセント・クリメント基地(St. Kliment Ohridski Base)からデセプション島(Deception Island)とサウス・ベイ(South Bay)にAnt-Planeを飛行させ,空中磁気観測と航空写真撮影を行った.デセプション島では,島の北半分9×18 kmの範囲を高度780 mで,3時間07分,302.4 kmを飛行し,空中磁気観測を行った.この結果からデセプション島の北半分とその周辺海域の磁気異常を明らかにすることができた.デセプション島とサウス・ベイでの飛行からは良好な画像が得られ,氷河の分布やその構造が撮影された.デセプション島の飛行は,無人機が南極の地平線を越えて科学観測をした数少ない飛行の1つである.暴風圏南端の過酷な自然条件の中で成功したことは,南極での無人飛行機による科学観測が可能であることを示した.また実機による航空機観測と比較し,極めて大きな費用対効果を実証した. Two small unmanned aerial vehicles, Ant-Plane 6 and Ant-Plane 3, were assembled using parts and technologies developed for model airplanes. The aerial vehicles were scheduled to conduct aero magnetic and photographic surveys of the Brans?eld Basin, from a takeoff runway at Marsh Air?eld on the South Shetland Islands, Antarctica, during January 2011. However, the scheduled surveys were not conducted on account of poor weather. Research was later conducted on a glacier, using a takeoff runway at St. Kliment Ohridski Base, Livingston Island, during December 2011. A ?ight from St. Kliment Ohridski Base to Deception Island yielded satisfactory results; the total distance of 302.4 km was traversed in 3 h 7 min (3:07). On this ?ight, aeromagnetic and aerial photographic data were obtained from an altitude of 780 m for a 9×18 km area on the northern half of Deception Island. Aerial photographs of Deception Island and South Bay showed the distributions of glaciers and their crevasses. The Ant-Plane ?ew over the Antarctic horizon and surveyed above Deception Island. That was the successful venture of this kind, demonstrating that airborne surveys by Ant-Planes are useful for Antarctic research investigations. Airborne surveys provide a safe and economical approach to data acquisition as compared with manned aerial operations. Errata | http://id.nii.ac.jp/1291/00010259/ departmental bulletin paper